2018
DOI: 10.1016/j.redox.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte hypertrophy induced by Endonuclease G deficiency requires reactive oxygen radicals accumulation and is inhibitable by the micropeptide humanin

Abstract: The endonuclease G gene (Endog), which codes for a mitochondrial nuclease, was identified as a determinant of cardiac hypertrophy. How ENDOG controls cardiomyocyte growth is still unknown. Thus, we aimed at finding the link between ENDOG activity and cardiomyocyte growth. Endog deficiency induced reactive oxygen species (ROS) accumulation and abnormal growth in neonatal rodent cardiomyocytes, altering the AKT-GSK3β and Class-II histone deacethylases (HDAC) signal transduction pathways. These effects were block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…Since low-concentrations of ROS induce cardiomyocyte growth [ 29 , 30 ], we treated H9C2 cells with various concentrations (20–300 µmol/L) of H 2 O 2 . We found a threshold concentration of 100 μmol/L H 2 O 2 at which the cell survival rate started to decline along with abnormal morphologic changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since low-concentrations of ROS induce cardiomyocyte growth [ 29 , 30 ], we treated H9C2 cells with various concentrations (20–300 µmol/L) of H 2 O 2 . We found a threshold concentration of 100 μmol/L H 2 O 2 at which the cell survival rate started to decline along with abnormal morphologic changes.…”
Section: Resultsmentioning
confidence: 99%
“…Overproduction of ROS following MI may lead to disruption in cell membrane integrity and increased permeability that causes leakage of intracellular enzymes, and necrosis and invasion of extracellular harmful substances into intracellular space [ 41 ]. However, moderate levels of ROS participate in cell signaling transduction that regulates cell growth and survival [ 29 , 30 ] and a delicate balance for optimal levels of ROS is critical for maintaining cardiac health and function. The precise regulatory mechanisms involving post-MI ROS generation and myocardial remodeling remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified Endog as a determinant of cardiac hypertrophy [ 14 ] and showed that spontaneously hypertensive rats, which naturally lack Endog expression, and Endog knockout mice, have increased ROS abundance in the heart and larger cardiomyocytes [ 14 ]. Our recent results show that EndoG is involved in the control of mtDNA replication and abundance, which influences mitochondrial ROS production, modulating cardiomyocyte size [ 15 ]. However the increase in cardiomyocyte size did not fully translate into increased heart mass in Endog -deficient mice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that reactive oxygen species (ROS), which are mainly generated in the mitochondrial respiratory chain, impair sperm production, motility, membrane, and DNA integrity and also influence sperm capacitation (Christova et al ., ; Henkel et al ., ; Brouwers et al ., ; Aitken et al ., ; Lee et al ., ). Humanin has been reported to prevent ROS accumulating in cardiomyocytes (Blasco et al ., ), cortical neurons (Cui et al ., ), retinal pigment epithelium (Minasyan et al ., ), and rat pancreatic beta cells (Paharkova et al ., ), etc. Pre‐treatment with humanin analog can exert cardiologically protective effects against myocardial ischemia and reperfusion injury in mouse models (Muzumdar et al ., ).…”
Section: Discussionmentioning
confidence: 99%